2016
DOI: 10.4103/0971-5916.192075
|View full text |Cite
|
Sign up to set email alerts
|

Impact of community-based health insurance in rural India on self-medication & financial protection of the insured

Abstract: Background & objectives:The evidence-base of the impact of community-based health insurance (CBHI) on access to healthcare and financial protection in India is weak. We investigated the impact of CBHI in rural Uttar Pradesh and Bihar States of India on insured households’ self-medication and financial position.Methods:Data originated from (i) household surveys, and (ii) the Management Information System of each CBHI. Study design was “staggered implementation” cluster randomized controlled trial with enrollmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 29 publications
3
18
1
Order By: Relevance
“…NHIS in Nigeria has succeeded in reducing, but not eliminating, deployment of extreme payment coping strategies in accessing major surgical operations. This apparently is due to significant co-payments and non-medical costs essentially similar to the finding from another community study in India by Dror et al, which shows that fewer households on community-based health insurance adopted borrowing to attend to direct non-medical costs associated with accessing needed healthcare when compared with households not covered by health insurance (23). Formal education has the propensity to increase household's prompt use of healthcare services and products, and to decrease household's dependence on borrowing and charity (24).…”
Section: Discussionsupporting
confidence: 78%
“…NHIS in Nigeria has succeeded in reducing, but not eliminating, deployment of extreme payment coping strategies in accessing major surgical operations. This apparently is due to significant co-payments and non-medical costs essentially similar to the finding from another community study in India by Dror et al, which shows that fewer households on community-based health insurance adopted borrowing to attend to direct non-medical costs associated with accessing needed healthcare when compared with households not covered by health insurance (23). Formal education has the propensity to increase household's prompt use of healthcare services and products, and to decrease household's dependence on borrowing and charity (24).…”
Section: Discussionsupporting
confidence: 78%
“…It was found in this study that some households were enrolled in the RSBY schemes through community visits of the respective government employees/officials rather than being voluntarily enrolled. Dror et al [23] reported that community-based health insurance was positively associated with household income and education of the head of the household. Education enhances skills and provides employment opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Ji et al (2017) used a cluster randomised design and found that CBHI reduced catastrophic health expenditures in Burkina Faso. Dror et al (2016b) also used a cluster randomised design and came to the same conclusion for India as well as establinshing lower prevalence of self medication amongst those supported by CBHI. Raza et al (2016), however, failed to establish a significant impact of CBHI in Uttah Pradesh and Bihar, India, using randomised control trials.…”
Section: Discussionmentioning
confidence: 99%